The Combination of Sonographic Features and the Seven-Gene Panel May be Useful in the Management of Thyroid Nodules With Indeterminate Cytology - Capezzone, Marco; Cantara, Silvia; Di Santo, Andrea; Sagnella, Alfonso; Pilli, Tania; Brilli, Lucia; Ciuoli, Cristina; Maino, Fabio; Forleo, Raffaella; Cartocci, Alessandra; Castagna, Maria Grazia (Frontiers in Endocrinology, 2021)
Introduction The management of patients with indeterminate thyroid nodules, which account for 10–25% of thyroid fine needle aspiration biopsies (FNABs), is still very challenging. Aim To verify the utility of the seven-gene panel in combination with ultrasound features in the clinical management of indeterminate thyroid nodules. Results The study group included 188 indeterminate thyroid nodules, divided into TIR3A (56.4%) and TIR3B (43.6%). A significant correlation between US categories and both cytological and molecular results was observed. In detail, TIR3B cytology was more frequent in EU-TIRADS 4 and 5 nodules (54.7 and 50%, respectively) than in EU-TIRADS 2 and 3 nodules (31%, p = 0.04). Similarly, the rate of a nodule with a mutation increased with the increase of US risk class (6.0% in EU-TIRADS 2 and 3, 9.3% in EUTIRADS-4 and 27.8% in EUTIRAD-5, p = 0.01). Among thyroid nodules submitted to surgery, final histology was benign in 61.4% nodules, while malignancy was diagnosed in 38.6% nodules. Using US score as tool for decision-making in TIR3A subgroup, we correctly classified 64.5% of thyroid nodules. The second tool (seven-gene panel test) was used in the subgroup of US high-risk nodules. By multiple tests with a series approach (US in all cases and US plus seven-gene panel in US high risk nodules) 84% of cases were correctly classified. In TIR3B nodules, using only seven-gene panel as tool for decision making, we correctly classified 61.9% of indeterminate nodules. By multiple tests with series approach (seven-gene panel in all cases and seven-gene panel plus US score in non-mutated nodules) only a slight improvement of thyroid nodule classification (66.6%) was observed. Conclusions US score seems able to correctly discriminate between TIR3A nodules in which a conservative approach may be used, and those in which additional test, such as molecular test, may be indicated. On the contrary, in TIR3B nodules both US risk stratification and seven-gene panel seem to be of little use, because the risk of thyroid cancer remains high regardless of US score and mutational status.